Things that move splashy coloring book - Dreamland publications (New Delhi : Dreamland publications, 2015)
"Things That Move: Splashy Coloring Book" is likely an activity book designed for young children. It probably features illustrations of various vehicles and modes of transportation, such as cars, buses, airplanes, and helicopters. The "splashy coloring" aspect suggests that the pages might be designed for use with water or special markers to create colorful effects with less mess. This type of book aims to combine fun and creativity with learning about different things that move.
Location: 2D
Keywords: Coloring book